Ti-Fe-Sn-Nb hypoeutectic alloys with superb yield strength and significant strain-hardening. (1st July 2017) - Zhao, Guo-Hua; Ketov, Sergey V.; Mao, Huahai; Borgenstam, Annika; Louzguine-Luzgin, Dmitri V.
Abstract: In this letter new Ti-Fe-Sn-Nb hypoeutectic alloy comprised of primary dendritic β-Ti and ultrafine (β-Ti + TiFe) eutectic was developed showing superior mechanical properties. The as-cast Ti67 Fe27 Sn3 Nb3 (at.%) alloy exhibited exceptionally high yield stress (2.18 GPa) comparable to that of bulk metallic glasses. Most importantly, the sample presented significant strain-hardening (320 MPa) and enhanced plasticity. The slip deformation and dislocation accumulation in the β-Ti dendrite contribute to the plasticity and the pronounced strain-hardening, whereas the high strength stems from the ultrafine (β-Ti + TiFe) eutectic structure as well as the solution hardening in the multicomponent system. Graphical abstract: